1993
DOI: 10.1192/bjp.162.3.393
|View full text |Cite
|
Sign up to set email alerts
|

The Nithsdale Schizophrenia Surveys. XI: Relatives' Expressed Emotion

Abstract: The level of expressed emotion (EE) in 32 relationships between relatives and schizophrenic patients was assessed on three separate occasions over five years. EE was high on all three occasions in 25% of relatives, low on all three in 38%, and fluctuating in 38%; that is, in the majority of relatives (63%) the level of EE was stable over time. Three relatives who had previously shown high EE had evidence of dementia at the time of the third assessment, and showed low EE. Fourteen patients relapsed at least onc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 18 publications
3
20
0
Order By: Relevance
“…Scazufca and Kuipers (1998) found 63.9% of stability in EE; 25% changed from high to low and 11% from low to high EE. McCreadie et al (1993) found 63% of stability over five years, but they also observed that the CFI may not be sensitive enough to measure EE out of crisis, or, if EE is only evident at times of crisis, then the CFI is not effective to evaluate its influence in the course of the illness. Another explanation is that the quality of the interactions would be different at times of crisis and out of crisis.…”
Section: Discussionmentioning
confidence: 92%
“…Scazufca and Kuipers (1998) found 63.9% of stability in EE; 25% changed from high to low and 11% from low to high EE. McCreadie et al (1993) found 63% of stability over five years, but they also observed that the CFI may not be sensitive enough to measure EE out of crisis, or, if EE is only evident at times of crisis, then the CFI is not effective to evaluate its influence in the course of the illness. Another explanation is that the quality of the interactions would be different at times of crisis and out of crisis.…”
Section: Discussionmentioning
confidence: 92%
“…After neuroleptic drugs introduction, the majority of psychiatric patients came back to live in their own social milieu. More symptomatic relapses were evident in these patients compared to subjects who did not live with their own families; in particular, families characterized by high emotional background seem to facilitate relapses [116]. …”
Section: Frequence and Risk Factorsmentioning
confidence: 99%
“…Recently, an increasing number of studies implicate family's EE as important factors influencing family relationships and dysfunction (Raune et al, 2004), and close relationships between EE and family functioning and distress have been established (Barrowclough and Parle, 1997). For some family caregivers, EE is not stable over time, regardless of whether they had participated in an intervention programme or not (McCreadie et al, 1993;Scazufca and Kuipers, 1999). However, Scazufca and Kuipers (1998) have reported that EE remained constant in two-thirds of the family members recruited and changes in EE levels in the families were predicted by changes in family burden and extent of contacts between patient and family within a 9-month follow-up period.…”
Section: Literature Reviewmentioning
confidence: 99%